Differences in Peak Oxygen Uptake in Bicycle Exercise Test Caused by Body Positions: A Meta-Analysis - Wan, Xiaohua; Liu, Chang; Olson, Thomas P.; Chen, Xiankun; Lu, Weihui; Jiang, Wei (Frontiers in Cardiovascular Medicine, 2021)
Background: As demand for cardiopulmonary exercise test using a supine position has increased, so have the testing options. However, it remains uncertain whether the existing evaluation criteria for the upright position are suitable for the supine position. The purpose of this meta-analysis is to compare the differences in peak oxygen uptake (VO2peak) between upright and supine lower extremity bicycle exercise. Methods: We searched PubMed, Web Of Science and Embase from inception to March 27, 2021. Self-control studies comparing VO2peak between upright and supine were included. The quality of the included studies was assessed using a checklist adapted from published papers in this field. The effect of posture on VO2peak was pooled using random/fixed effects model. Results: This meta-analysis included 32 self-control studies, involving 546 participants (63% were male). 21 studies included only healthy people, 9 studies included patients with cardiopulmonary disease, and 2 studies included both the healthy and cardiopulmonary patients. In terms of study quality, most of the studies (n = 21, 66%) describe the exercise protocol, and we judged theVO2peak to be valid in 26 (81%) studies. Meta-analysis showed that the upright VO2peak exceeded the supine VO2peak [relative VO2peak: mean difference (MD) 2.63 ml/kg/min, 95% confidence interval (CI) 1.66-3.59, I2 = 56%, p < 0.05; absolute VO2peak: MD 0.18 L/min, 95% CI 0.10-0.26, I2 = 63%, p < 0.05). Moreover, subgroup analysis showed there was more pooled difference in healthy people (4.04 ml/kg/min or 0.22 L/min) than in cardiopulmonary patients (1.03 ml/kg/min or 0.12 L/min). Conclusion: VO2peak in the upright position is higher than that in supine position. However, whether this difference has clinical significance needs further verification. Systematic Review Registration: identifier, CRD42021233468.